Identification of the Cytokinin-Active Ribonucleosides in Pure Escherichia coli tRNA Species - Bartz, J. (1970)
The distribution of the two cytokinin-active ribonucleosides 6-(3-methyl-2-butenylamino)-9-β-D-ribofuranosylpurine (1) and 6-(3-methyl-2-butenylamino)-2-methylthio-9-β-D-ribofuranosylpurine (2) in tRNA(Phe), tRNA(UUG)(Leu), tRNA(UCR)(Ser), tRNA(Tyr), tRNA(Cys), and tRNA(2)(Trp) from stationary phase Escherichia coli has been studied. Compound 2 predominated in all these species except tRNA(Phe), in which compound 1 was greatly in excess. Compound 1 was present in relatively small amounts in tRNA(UUG)(Leu), tRNA(Cys), and tRNA(2)(Trp), and was not detected in tRNA(UCR)(Ser) and tRNA(Tyr). Cells from the early logarithmic phase had the highest cytokinin content in their tRNA. Stationary phase tRNA had a slight increase in the amount of 1, which may be explained by the appearance of the new tRNA(Phe). No differences were observed between the chromatographic patterns of tRNAs from early-, mid-, and latelogarithmic phases.